2013
DOI: 10.1093/reseval/rvt010
|View full text |Cite
|
Sign up to set email alerts
|

The PhD track: Who succeeds, who drops out?

Abstract: Doctoral completion rates are an indicator of successful doctoral programmes and of a region's potential of highly skilled workforce. The Human Resources in Research -Flanders (HRRF) database contains data of all academic staff appointments, doctoral student registrations and doctoral degrees of all Flemish universities from 1990 on. Previous research has identified the following factors as affecting successfully completing the Ph.D.: cohort, scientific discipline, type of scholarship or appointment, gender, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
2
16

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(80 citation statements)
references
References 15 publications
4
49
2
16
Order By: Relevance
“…Several authors found that men are (slightly) more likely to complete their doctorate than women, sometimes even when other factors are taken into account such as the scientific discipline (Groenvynck, Vandevelde, & Van Rossem, 2013;Van Ours & Ridder, 2003;Visser, Luwel, & Moed, 2007). Other authors found no effect of gender on doctoral completion (Mastekaasa, 2005;Van der Haert, Arias Ortiz, Emplit, Halloin, & Dehon, 2013;Wright & Cochrane, 2000;Spronken-Smith, Cameron, & Quigg, 2018).…”
Section: Factors Related To Doctoral Completionmentioning
confidence: 99%
“…Several authors found that men are (slightly) more likely to complete their doctorate than women, sometimes even when other factors are taken into account such as the scientific discipline (Groenvynck, Vandevelde, & Van Rossem, 2013;Van Ours & Ridder, 2003;Visser, Luwel, & Moed, 2007). Other authors found no effect of gender on doctoral completion (Mastekaasa, 2005;Van der Haert, Arias Ortiz, Emplit, Halloin, & Dehon, 2013;Wright & Cochrane, 2000;Spronken-Smith, Cameron, & Quigg, 2018).…”
Section: Factors Related To Doctoral Completionmentioning
confidence: 99%
“…The PhD student's relationship with the faculty, particularly with his or her advisor, can determine success in the student's academic program as well as in the student's professional career. For example, studies show that positive student qualities (Ho et al, 2010), their commitment to research and writing research articles (Humphrey, Marshall, & Leonardo, 2012), involvement in academic conferences (Bolli, Agasisti, & Johnes, 2015), having good scientific discipline (Groenvynck, Vandevelde, & Van Rossem, 2013), and having good interpersonal working relationships with advisors (Ives & Rowley, 2005) can determine success in their academic program as well as in their professional career. Also, gender and language proficiency levels are sometimes ÜNİVERSİTEPARK Bülten | Bulletin • Volume 6 • Issue 1 • 2017 mentioned as reasons (Lebcir, Wells, & Bond, 2008;Rodwell & Neumann, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…For example, studies show that positive student qualities (Ho et al, 2010), their engagement with research training (Humphrey et al, 2012), participation in graduate conferences (Bolli et al, 2013) having good scientific discipline (Groenvynck et al, 2013), having good interpersonal working relationships with supervisors (Ives and Rowley, 2005) play key roles in their academic success. Other reasons that are often quoted include language proficiency levels (Lebcir et al, 2008;Rodwell and Neumann, 2008) and gender.…”
Section: Introductionmentioning
confidence: 99%